2022
DOI: 10.1021/acsami.2c12061
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Polyamide Nanofiber Membranes with Interconnective Amphiphobic Channels for Seawater Desalination

Abstract: Seawater desalination is a promising and sustainable solution to alleviate freshwater scarcity; however, most existing desalination membranes suffer from poor channel interconnectivity and toxic solvent processing and encounter a tradeoff dilemma of salt rejection and water flux. Herein, we report a unique and facile one-step green solvent/nonsolvent spinning methodology to assemble environmentally friendly polyamide nanofiber membranes with a precisely designed interconnective/stable channel structure and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Essential oils derived from natural sources are generally considered bioactive and biocompatible [175]. When integrated into nanofiber materials, they are less likely to cause adverse reactions or toxicity, making them suitable for biomedical applications like tissue engineering, drug delivery, and wound healing [176][177][178]. Wang et al [179] selected clary sage and black pepper essential oils to prepare PLA nanofiber, and studies have shown that these essential oils impart antibacterial, anti-inflammatory, or anti-oxidant properties on electrospun fibres.…”
Section: Bioactive and Biocompatiblementioning
confidence: 99%
“…Essential oils derived from natural sources are generally considered bioactive and biocompatible [175]. When integrated into nanofiber materials, they are less likely to cause adverse reactions or toxicity, making them suitable for biomedical applications like tissue engineering, drug delivery, and wound healing [176][177][178]. Wang et al [179] selected clary sage and black pepper essential oils to prepare PLA nanofiber, and studies have shown that these essential oils impart antibacterial, anti-inflammatory, or anti-oxidant properties on electrospun fibres.…”
Section: Bioactive and Biocompatiblementioning
confidence: 99%
“…As a membrane for seawater desalination, environmentally friendly alcohol-based polyamide mats were realized via one-step green solvent/non-solvent electrospinning by directly incorporating the fluorinated chemical into spinning solutions. The resultant polyamide nanofiber membranes exhibited high vapor permeation, good tensile strength, and elongation, thus permitting robust seawater desalination performance with remarkable salt rejection (99.97%) [ 96 ].…”
Section: Blended and Composite Fibers Towards Bio-sustainabilitymentioning
confidence: 99%
“…Fresh water shortage represents one of the foremost challenges facing the world . Among the varied technologies developed to overcome this challenge, sorption-based atmospheric water harvesting (AWH), water extraction from the ambient air with sorbents, has attracted particular interest due to its advantageous features in energy efficiency, relatively less climate dependence, and a wide range of geographic applicability. To date, a great number of sorbents such as hygroscopic salts, polymer aerogels, active carbons, and metal–organic frameworks (MOFs) have been widely explored for AWH. Of them, MOFs have been identified as an important type of AWH sorbents particularly suitable for AWH in arid areas due to their outstanding atmospheric water adsorption at low relative humidity (RH), low energy input for regeneration, and well tailorable surface and porosities for adaptive AWH. MOF-based AWH follows a temperature-swing adsorption (TSA) principle: atmospheric water adsorption at ambient temperature and water desorption at elevated temperature with external heating sources. Effective MOF heating, therefore, plays a critical role in determining the water productivity and energy cost of MOF-based AWH. …”
Section: Introductionmentioning
confidence: 99%